1991
DOI: 10.1111/j.1365-2362.1991.tb01420.x
|View full text |Cite
|
Sign up to set email alerts
|

Leukotriene B4 levels from stimulated neutrophils from healthy and allergic subjects: effect of platelets and exogenous arachidonic acid

Abstract: Leukotriene B4 (LTB4) levels were measured in peripheral blood neutrophils from allergic and healthy donors after stimulation by calcium ionophore A 23187. This level was higher in neutrophils from allergic subjects than in neutrophils from healthy subjects in the presence as well as in the absence of exogenous arachidonic acid. Platelets from allergics increased LTB4 levels from neutrophils from allergics but not levels in those from healthy donors. Moreover, platelets from healthy subjects reduced LTB4 in ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
1
14
0
Order By: Relevance
“…This persistent inhibition of neutrophil LTB 4 synthesis by platelets in the presence of MSUM indicates that adenosine was not responsible for the inhibitory effect and suggests that another platelet product is involved in such an effect. This pattern is reminiscent of (a) a significant inhibition by platelets of the LTB 4 synthesis from A23187-stimulated neutrophils (Hosni et al, 1991), of (b) the absence of effect of adenosine on LTB 4 synthesis by neutrophils activated by ionophore A23187 as previously reported (Krump et al, 1997), and of (c) the absence of inhibition by adenosine of phospholipase D stimulated by MSUM in human neutrophils (Thibault et al, 2000).…”
Section: Chabannes Et Almentioning
confidence: 54%
See 4 more Smart Citations
“…This persistent inhibition of neutrophil LTB 4 synthesis by platelets in the presence of MSUM indicates that adenosine was not responsible for the inhibitory effect and suggests that another platelet product is involved in such an effect. This pattern is reminiscent of (a) a significant inhibition by platelets of the LTB 4 synthesis from A23187-stimulated neutrophils (Hosni et al, 1991), of (b) the absence of effect of adenosine on LTB 4 synthesis by neutrophils activated by ionophore A23187 as previously reported (Krump et al, 1997), and of (c) the absence of inhibition by adenosine of phospholipase D stimulated by MSUM in human neutrophils (Thibault et al, 2000).…”
Section: Chabannes Et Almentioning
confidence: 54%
“…Thrombinactivated platelets are also able to increase LTB 4 synthesis by human blood neutrophils stimulated with fMLP, PAF, or C5a through a mechanism independent of platelet 12-LOX and COX, possibly through plateletderived AA (Palmantier and Borgeat, 1991), or to increase LTB 4 synthesis by rabbit blood neutrophils stimulated with fMLP through AA originating from platelets (Evangelista et al, 1999). However, human platelets added to neutrophils in the presence of ionophore A23187 can slightly increase LTB 4 accumulation while decreasing that of 5-HETE (McCulloch et al, 1992) or can decrease LTB 4 synthesis (Maderna et al, 1993), an effect not observed in allergic patients (Hosni et al, 1991). These controversial data prompted us to study the effect of human platelets on blood neutrophils to verify whether the platelet inhibitory effect on LTB 4 formation could be demonstrated in conditions using pathophysiologic agonists such as fMLP and MSUM.…”
Section: Chabannes Et Almentioning
confidence: 99%
See 3 more Smart Citations